Evaluating grease trap management practices: a case study from Seri Kembangan, Malaysia - Lee, Li Xin; Mohamed Fauzi, Nur Fatihah Eliya; Roslan, Ahmad Muhaimin; Ariffin, Hidayah; Mohd Yusoff, Mohd Zulkhairi; Ramli, Norhayati; Abdul Mutalib, Noor Azira (Academic Press, 2025)
Sewerage blockages due to oil and grease deposition discharged from food premises remain a persistent issue globally. This study evaluates the degree of compliance of food premises in Seri Kembangan, Selangor, Malaysia with grease trap guideline, and investigates the factors affecting restaurants' compliance performance. Data were collected from 36 restaurants through a questionnaire-based interview consisting of questions about grease trap installation, operation, maintenance and waste disposal, followed by a walkthrough of the kitchen. Results show that 72.22% of food premises' compliance levels were good, 5.56% were excellent, 13.89% were moderate and 8.83% were poor. Food premises equipped with appropriate facilities and financial resources execute grease trap practices more diligently. A significant association was observed between location with compliance level (p < 0.05) determined via Fisher's Exact Test. This study revealed the grease trap practice gaps and provided a basis for improving regulations and enforcement.